The influence of Employee Competency, Job Stress, Work Environment, and Performance Appraisal System toward Employee Performance at Kantor Pelayanan Pajak Pratama in Metro - Ardiansyah - Japlani; Eva - Purnamasari (Admisi dan Bisnis, 2020)
The research objective is to determine the influence of employee competency, job stress, work environment, and performance appraisal system together to have a significant influence on employee performance at the Pratama tax service office in Metro and to find out the most significant variables affecting employee performance in the Pratama tax service office in Metro.The population of this research were all employees of KPP Pratama, Metro Lampung City. This research was conducted through filling in the employee questionnaire. The research respondents were 50 employees who worked in Pratama tax service office in Metro. The sampling technique in this research used random sampling, while for the method of data analysis and hypothesis testing, the researcher used multiple linear regression methods supported by the SPSS version 20 program.The results of the research show that: 1) employee competency has a positive influence on employee performance 2) job stress has a negative effect on employee performance 3) work environment negatively affects employee performance 4) performance appraisal system has a negative effect on employee performance The results of the study simultaneously showed that the research on employee competency, job stress, work environment, and performance appraisal systems did not significantly influence employee performance.